Politeness Maxims Analyzed in Taulany TV's Vlog, Showcasing Ayu Ting Ting's Large House - Mariska, Revi (CV. Akademi Merdeka, 2025)
This research aims to analyse the application of the maxim of politeness in Taulany TV vlogs, focusing on the episode featuring Ayu Ting Ting's house. The method used is qualitative content analysis of vlog videos by selecting relevant vlog samples and analysing conversation transcriptions to identify the application of the maxim of politeness. The results show that deviations from the maxim of quantity and maxim of relationship often occur when the speaker provides more information than necessary or makes statements that are not directly relevant to the previous discussion. This research provides new insights into the adaptation of the politeness maxim in the context of vlogs and emphasizes the importance of considering contextual factors in digital communication. It also contributes to the development of more effective and ethical communication theories.